Star 0Happy : A New Civilization: The Instant Mass Strategy to Overcome Coronavirus, Fears, and Hunger in Various Countries - Gunawan, Cakti Indra (International Research & Development for Human Beings (IRDH), 2024)
The author expresses gratitude to God the Most Gracious and Merciful for all His gifts so that this book can be published. The infinite words belong to the writer's parents, Mrs. Sri Rejeki and Mr. Mino, who always pray for the author's happiness and successes every time and every day. With intercession and prayer from the author's spiritual teacher, the late Prof. Dr. H SS Kadirun Yahya, and YM Ustadz Danish Lutfi, this book can be completed well. The author also gives thanks to author's teachers since kindergarten, elementary school to high school teachers, as well as the lecturers of writers ranging from undergraduate (S1), master (S2) to the doctorate (S3). The authors also thank to thank the big family of Bani Mino, Marsiyo Karsomartejo, Karso Prawiro, fellow lecturers, researchers, scholars, government officials, politicians, military, police, and all elements who have supported and succeeded in this book to be able to give a drop of hope for humankind that is being hit by the corona disaster in various corners of the world. To my students and young people around the world who read this book, the author hopes that the star civilization of humankind will be held by young people who have the spirit of stars, the sense of sharing goodness for humanity without recognizing differences. Covid-19 (in this book written as coronavirus) in early 2020 caused fear and hunger of humanity in almost all countries in the world. The author realizes that at this time, what is needed by humankind throughout the world is happiness, peace, no more people who die of hunger, and no chaos that results in crime in some countries. The Star 0Happy formula is a practical solution offered by the author based on the results of research and the author's experience concerning the dynamics of human life. After reading this book, it is expected that there will be peaceful and sharing activity among human beings so that it will have an impact on reducing hunger. This book is written in a language that is easily understood and practiced by all groups without knowing differences in religion, nation, ethnicity, class, age, and social status. This book is different from other similar books that discuss coronavirus because this book uses a solution approach from within humans, the Star 0Happy formula, which consists of 0 (apologize), 29 (grateful), and Star (alms). The author realizes this book is still lacking, but hopefully can provide benefits and blessings to humanity, Amen. One more thing, by buying this book, you have made a tremendous investment because you will get happiness and benefits whose value cannot be compared with any material value.